2020
DOI: 10.1108/ijppm-11-2019-0524
|View full text |Cite
|
Sign up to set email alerts
|

Enablers of green business process management in the oil and gas sector

Abstract: PurposeThe integration of green business process management (GBPM) to the existing processes of the oil and gas companies (O&G) in the Gulf Cooperation Council (GCC) countries can lower environmental damage in the O&G sector (OGS), which causes more environmental hazards than other sectors. Studies suggest that sustainability remains a challenge for GCC O&G companies. In this context, this study assesses the following enablers and subenablers related to GBPM integration in these companies: strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Organizations around the globe recognize that performance is an important element for business growth and sustainability (AlNuaimi et al , 2020; Epstein and Roy, 2001; Sproul et al , 2019). Prior research has identified important aspects of firm performance, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Organizations around the globe recognize that performance is an important element for business growth and sustainability (AlNuaimi et al , 2020; Epstein and Roy, 2001; Sproul et al , 2019). Prior research has identified important aspects of firm performance, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, these processes are technically challenging, and overcoming such challenges would ensure the economic competitiveness of SAJF produced on a large scale. This is a crucial RI of a TeDP system, as system operation using low-cost fuel would significantly reduce operational costs (AlNuaimi et al , 2020; DiNovo, 1978; Dryer, 2014; Propulsion et al , 2016). As such, this RI affects the operational outcomes of the entire system.…”
Section: Results Indicatorsmentioning
confidence: 99%
“…The GI philosophical originates from the green principle and CSD, representing the relationship between the environment and a firm's operations (Shahzad et al, 2020), and provides critical information on an organization's processes and environmental regulations compliance (Xie et al, 2019). Prior studies (AlNuaimi et al, 2020;Yuan and Xiang, 2018) stated that firms must transform their processes into eco-responsive activities by introducing essential reforms in operational product processes to be green organizations. Therefore, the following hypotheses are proposed: H2.…”
Section: Green Innovation Corporate Sustainability Development and To...mentioning
confidence: 99%